Analisis Tingkat Kepuasan Petani Terhadap NPK Singkong 17-6-25 Pusri di Kecamatan Banjar Margo Kabupaten Tulang Bawang, Lampung - Pujiati, Pujiati; Antoni, Mirza; Purbiyanti, Erni (Fakultas Pertanian Universitas Mataram, 2025)
High crop productivity can be achieved by using specific fertilizers according to the needs of crops and land fertility such as NPK Cassava 17-6-25 which is specifically designed to increase the productivity of cassava plants. This study aims to analyze the level of farmers' satisfaction with the 17-6-25 Pusri Cassava NPK in Banjar Margo District, Tulang Bawang Regency, Lampung. The selection of the research location used the purposive sampling method by involving 100 cassava farmers as respondents. Primary data was collected through a structured survey using a questionnaire and analyzed using the Customer Satisfaction Index (CSI) method. The results showed that cassava farmers who used NPK Sinkong 17-6-25 fertilizer were mostly satisfied with its quality and performance, which was shown by a satisfaction score of 81%. Attributes related to the quality and nutritional content of fertilizers received the highest ratings, reflecting that this fertilizer successfully met farmers' expectations. This indicates that 17-6-25 Cassava NPK fertilizer is an effective choice for farmers in improving the yield and quality of their cassava crops.